The structural integrity of corroded concrete sewers. (October 2019) - Kuliczkowska, Emilia; Parka, Anna
Abstract: The objective of the study was to analyse the relationship between the rate of corrosion and the structural integrity of old corroded concrete sewer pipes by employing different methods of calculation of the loads acting on the pipes. The article discusses factors affecting corrosion of sewer pipes and provides examples to illustrate its various rates. The four methods used in the analysis of the ring bending tensile strengths of sewer pipes differ in the assumptions concerning the determination of the size and distribution of loads acting on the pipes. The results of two case studies were used to assess how the rate of corrosion influences the structural integrity of sewer pipes. Another objective of the analysis was to check whether the prioritisation of sewers for renewal based on a method that involves determining categories of sewer failure probability due to corrosion is correct. The key conclusion is that the method based on the categories of failure probability is not always suitable to assess the structural integrity of sewer pipes and that the corrosion of the pipe walls does not always have a deteriorating effect on the structural integrity of the pipes. In some cases of tight sewer pipes around which there have been rheological transitions in the soil, the structural integrity of the pipes may improve despite the corrosion of the pipe walls. Graphical abstract: Unlabelled Image Highlights: Internal corrosion is a serious problem in concrete sewers. Soil parameters may not have a negative effect on the structural integrity of sewers. Rheological transitions may improve the structural integrity of corroded sewers. It is important to select an adequate method for static calculation of sewers.